Characterization of phosphate processing sludge from Tunisian mining basin and its potential valorization in fired bricks making. (15th February 2021) - Ettoumi, M.; Jouini, M.; Neculita, C.M.; Bouhlel, S.; Coudert, L.; Taha, Y.; Benzaazoua, M.
Abstract: Reuse of mine waste as alternative raw material in the construction sector is a promising environmental solution. The aim of this study was to evaluate the potential use of phosphate sludge as alternative raw material in the production of fired bricks, while substituting the natural finite clay soils. Representative samples of phosphate processing sludge were collected and characterized. Then, raw materials, consisting of 100% phosphate sludge, were fired at three temperatures (900, 1000, and 1100 °C) for bricks' making. Fired bricks were then characterized. Results showed that the sludge was non-plastic and mainly composed of fluoroapatite (∼16%), calcite (∼23%) and clays (∼22%). An improvement in bricks porosity (∼31%), firing shrinkage (∼31%), water absorption (∼27%), and flexural strength (∼71%) was observed with the increase of firing temperature from 900 to 1100 °C. Optimal properties of fired bricks were obtained at 1100 °C, with porosity of 9%, firing shrinkage of 7.5%, water absorption of 12.5%, bulk density of 1.4 g/cm 3 and flexural strength of 13.4 MPa. All properties of fired bricks complied with the construction material standards. With respect to the environmental behavior, metal concentrations met the requirements for the potential mobility and toxicity of contaminants. Therefore, production of bricks from phosphate sludge is a promising option for the sustainable management of these residual, valueless and abundant materials, to preserve soils that are currently often overexploited for their disposal, to reduce their environmental footprints and to minimize the exploitation of non-renewable resources already used in bricks' manufacturing. Graphical abstract: Image 1 Highlights: Phosphate processing sludge as raw material for fired brick making was evaluated. Fired bricks were baked from 100% of phosphate sludge at 900 °C, 1000 °C, and 1100 °C. Phosphate sludge was non-plastic and mainly composed of fluoroapatite, calcite, and clays. Bricks porosity, firing shrinkage, water absorption, and flexural strength increased with firing temperature. All properties of fired bricks complied with the construction material standards.